Culture as Tourism Attraction: Commodi cation and Politicization of Culture in Kembangarum Tourism Village, Yogyakarta Special Region, Indonesia - Raden Rucitarahma Ristiawan (Gadjah Mada Journal of Tourism Studies, 2018)
This study aims at describing the commodi cation processes and the form of politicization of culture used as the background of tourism village development toward several community empowerment activities. Employing a case of Kembangarum Tourism Village, Turi District, Sleman Regency, Yogyakarta Special Province, Indonesia, the commodi cation processes are examined in several forms of tourism attractions based on local Javanesse tradition. Commodi cation of culture practices in Kembangarum Tourism Village are encouraged by the politicization of culture represented by several policies and events provided by local government as the background of Kembangarum Tourism Village development direction. This study nds the commodi cation processes as a part of politicization of culture encompassed in community empowerment agendas. There are several models of community empowerment initiated by the investor to put his capital of investment as bene cial as he wants. The development model of Kembangarum Tourism Village through investment projects by the developer results in community con icts encouraged by the local traditions that have been privatized by the investor. This study also delivers the suggestion of development direction that will be provided by government in the future.